1998
DOI: 10.1046/j.1365-2273.1998.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble adhesion molecules in middle ear effusions from patients with chronic otitis media with effusion

Abstract: Soluble forms of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) have been identified in the peripheral blood and other body fluids. These soluble adhesion molecules have been reported to reflect the upregulation of cell surface ICAM-1 and VCAM-1 expression in inflammatory diseases. The levels of soluble ICAM-1 and soluble VCAM-1 in 37 middle ear effusions from 37 patients with chronic otitis media with effusion (OME) were quantitatively determined with enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…PAF also stimulates secretion of mucus glycoprotein mediated by arachidonic acid metabolites, especially metabolites of the lipoxygenase pathway via a PAF-receptor dependent mechanism (244), and inhibits mucociliary clearance of the eustachian tube (245). The expression of soluble adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1), is known to be upregulated at the cell surface in inflammatory disease.…”
Section: Inflammation and Ommentioning
confidence: 99%
“…PAF also stimulates secretion of mucus glycoprotein mediated by arachidonic acid metabolites, especially metabolites of the lipoxygenase pathway via a PAF-receptor dependent mechanism (244), and inhibits mucociliary clearance of the eustachian tube (245). The expression of soluble adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1), is known to be upregulated at the cell surface in inflammatory disease.…”
Section: Inflammation and Ommentioning
confidence: 99%
“…Different groups of inflammatory mediators were identified in the human middle ear mucosa, fluids and effusions. A lot of different mediators participate in initiation and early stages of the middle ear inflammation, including arachidonic acid metabolites (prostaglandin E 2 and leukotrienes LT-B 4 , LT-C 4 ), 75,76 histamine, 77,78 platelet-activating factor, 79 surface cell adhesion molecules (intercellular adhesion molecule-1, vascular cell adhesion molecule-1, endothelial leukocyte adhesion molecule-1, platelet endothelial cell adhesion molecule), 80,81 soluble cell adhesion molecules (soluble intercellular adhesion molecule-1 and soluble vascular cell adhesion molecule-1), 82,83 chemokine RANTES, 84 complement C3a anaphylatoxin 85 and interferon-g. 86 However, cytokines are the key mediators of the middle ear inflammation. Cytokines regulate different stages of inflammation, are responsible for resolution of inflammation and can initiate local molecular processes leading to histopathological changes in the middle ear mucosa and submucosa, and the chronic condition of otitis media.…”
Section: Introductionmentioning
confidence: 99%
“…The present results are comparable to previous reports. 4–7,9,13 To our knowledge, we present the largest OME study group described. In accordance with our study, a high correlation among endotoxin, TNFα, and IL1β was recently reported in a similar patient group.…”
Section: Discussionmentioning
confidence: 99%
“… 6 There is only one previous report of adhesion molecules in middle ear effusions describing a correlation between ICAM‐1 and VCAM‐1 like in our findings. 13 The variation in concentration ranges between studies could be the result of different inclusion criteria along with features of the measuring methods, including sensitivity and detection percentage. We wanted to include chronic OME cases, excluding AOM and recurrent AOM cases.…”
Section: Discussionmentioning
confidence: 99%